Vulnerabilidade às inundações em Teresina, Piauí - Chaves, Sammya Vanessa Vieira [UNESP] (2015)
The lack of urban planning, the increase of the population in the urban areas culminating in the occupation of areas inadequate to build houses, can be considered as factors that have contributed to the increase in the number of people affected by the natural disasters throughout the years. In Brazil, there is no natural tendency for tectonic origin phenomenon, such as earthquakes and volcanoes, however, the records of disasters resulting from climate variability and atmospheric instability, such as droughts, floods and landslides are frequent. Among these disasters, the floods are the most recurring and when they happen in the dense urban centers, the troubles become more aggravated. In Teresina, capital of the state of Piauí, just like many other Brazilian counties, the floods are frequent in specific parts of the city during the rainy season, which goes from January to May. In view of the above, it's intended with this research, to analyze the vulnerability to floods in Teresina, by the light of the characteristics of its urban site, the functions of the city and its environment, pointing out the areas with the most recurring episodes and the profile of the affected population. Studies about the vulnerability in urban areas are becoming, in the recent years, a valuable instrument used by many scholars in order to point out the areas of the city in which the population is susceptible to any disaster that can compromise their quality of life and the importance of these studies goes through the fact that they can subsidize public policies that minimize the problems of less fortunate segments of the townspeople that are susceptible to many disasters. In order to achieve this, we used as methodological procedures the making of a theoretical referential approaching the concepts of natural disasters, their types and occurrences in the world and in Brazil, as well as the application of questionnaires in segments considered vulnerable to...